2009
DOI: 10.1159/000240018
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis Rubra Pilaris with Preceding Cytomegalovirus Infection

Abstract: Pityriasis rubra pilaris (PRP) is a papulosquamous disorder comprising 6 clinical types. Some factors – including abnormal vitamin A metabolism, internal malignancies, autoimmune diseases, infection and trauma – are thought to be involved in the etiology. Recently, human immunodeficiency virus (HIV)-associated PRP has been reported to have distinct clinical features, such as nodulocystic acne and lichen spinulosus alongside PRP. We report here the case of a 38-year-old female with onset of classical PRP after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
15
0
3
Order By: Relevance
“…[6][7][8] Accepted triggers of PRP are viral or bacterial infections. [9][10][11][12][13][14] The successful treatment of PRP with antiretroviral drugs in HIV-positive patients can be especially placed as a standard therapeutic measure. 15 Anecdotal reports suggest that autoimmune diseases 16,17 and neoplasias [18][19][20][21][22][23] can trigger PRP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Accepted triggers of PRP are viral or bacterial infections. [9][10][11][12][13][14] The successful treatment of PRP with antiretroviral drugs in HIV-positive patients can be especially placed as a standard therapeutic measure. 15 Anecdotal reports suggest that autoimmune diseases 16,17 and neoplasias [18][19][20][21][22][23] can trigger PRP.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the understanding is that PRP is not a consequence of vitamin A deficiency, but rather it is responsive to alitretinoin, isotretinoin etretinate, and vitamin A . Accepted triggers of PRP are viral or bacterial infections . The successful treatment of PRP with antiretroviral drugs in HIV‐positive patients can be especially placed as a standard therapeutic measure .…”
Section: Aetiology and Pathologymentioning
confidence: 99%
“…On the other hand, viral infections may also trigger PRP. Kawara et al . reported a case of PRP that occurred following cytomegalovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, viral infections may also trigger PRP. Kawara et al 12 reported a case of PRP that occurred following cytomegalovirus infection. They indicated that some viral or bacterial infection may produce modification of immune responses in the Th1 pathway and inflammation of skin as a target, and may lead to the development of PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ultraviolet B phototherapy exacerbated the disease in some patients [7]. Recent observations also point to triggering comorbidities including HIV or cytomegalovirus infection, chronic hepatitis C, myasthenia gravis, sprue, hypothyroidism, neoplasia or trauma [3,8]. Leukemia-associated forms have been reported repeatedly [9].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%